Effectiveness of Mental Development of Prisoners in Cirebon Narcotics Prison Class IIA as a Form of Correctional Purposes - Hamja, H (Faculty of Law, Universitas Jenderal Soedirman, 2019)
The number of Narcotics-abuse continues to increase, for example needles and the making of tattoos, narcotics dependence not only causes a physical but also psychological impact on a person. The problem of this research was about the mental formation of prisoners and the model of their formation in the Cirebon Narcotics Prison. This research was an empirical study and the data collection included survey, observation, interview and literature studies. The data were qualitatively analyzed by descriptive method. The research findings indicated that mental coaching required operational guidance including, methadone programs, community therapy, coaching involving the community and Criminon Indonesia training programs. The mental development of Narcotics Prisoners has not fully implemented methadone and community therapy program; Criminon training has been fulfilled while the other has not. Guidance for prisoners must be integrated among the prison staff, the community and prisoners as well.Keywords: Prisoners, Prisons, Mental Development